Extended cubic B-spline method for linear two-point boundary value problems - Nur Nadiah Abd Hamid,; Ahmad Abd. Majid,; Ahmad Izani Md. Ismail, (Universiti Kebangsaan Malaysia, 2011)
Second order linear two-point boundary value problems were solved using extended cubic B-spline interpolation method. Extended cubic B-spline is an extension of cubic B-spline consisting of one shape parameter, called λ. The resulting approximated analytical solution for the problems would be a function of λ. Optimization of λ was carried out to find the best value of λ that generates the closest fit to the differential equations in the problems. This method approximated the solutions for the problems much more accurately compared to finite difference, finite element, finite volume and cubic B-spline interpolation methods.